ARTIFICIAL INTELLIGENCE : AN OPPORTUNITY FOR SUSTAINABLE AGRICULTURE IN CÔTE D’IVOIRE ? - KOUAKOU, Bah Isaac; ABOUTOU, Akpassou Isabelle (Revue Internationale du Chercheur, 2025)
Abstract: Agriculture is a key sector of the Ivorian economy, representing 54.6% of the added value of the primary sector and contributing 7.8% to GDP in 2023 (Agence Nationale de la Statistique et de la Démographie, Côte d’Ivoire). Faced with environmental and economic challenges, it seeks to adopt sustainable practices to ensure its longevity (Koffi, 2023). Artificial Intelligence (AI) emerges as a promising solution to optimize agricultural production. This research, based on interviews with 11 agricultural cooperative leaders in the Nawa region, analyzes farmers’ perceptions of AI and the challenges related to its use. The results indicate that AI enhances yields by optimizing resources such as water and fertilizers. It promotes more ecological agriculture by reducing pesticide use to essential levels. Additionally, AI automates processes like soil analysis, product sorting, and disease detection, ensuring efficiency and precision. It also facilitates fast and uniform pesticide and fertilizer spraying, helping farmers optimize their time and work. Integrating AI into agriculture could thus foster more sustainable production while improving farming practices.